Gender differences in suicide in Serbia within the period 2011–2015 - Dedić, Gordana J.; Dedić, Srdjan (Vojnosanitetski pregled, 2021)
Background/Aim. The World Health Organisation (WHO) estrimates that approximately 1,000,000 people die by suicide every year. The aim of this study was to examine the gender differences in cases of committed suicides, including suicide rates, socio-demographic factors and methods of suicide in Serbia within the period 2011–2015. This investigation is continuing the previous investigation from the period 2006–2010. Methods. Data were obtained from the Statistical Office of the Republic of Serbia. Their classification related to the suicide method was carried out on the basis of International Classification of Diseases-Tenth Revions-Clinical Modification (ICD-X-CM) (WHO 1992). Statistical analysis was done by using the crude number of committed suicide. Results. Within the period 2011–2015, the total number of suicides in Serbia was 5,897, of which 74.56% were males and 25.44% females (male to female suicide ratio was 2.93). Annual suicide rate (per 100,000) showed constantly decreased from 2011 to 2015, and in 2015 it was 15. Male/female suicide ratio was the highest among adolescents and decreased with age. The suicide was the most often committed by married males (47.6%) and widowed females (38.86%) with completed high school, retired, Serbs. About a quarter (23.38%) suicide committers were older than 75 years, and 39.39% were older than 65 years. The most common suicide method males (64.63%) and females (59.00%) used was hanging, strangulation and suffocation. The second most common method males used was by firearm (18.96%) and females by poisoning (16.73%). Conclusions. Suicide Prevention Programme in Serbia should be primarily oriented towards two age groups at highest risk to commit suicide, towards the adolescents whose suicide was on the rise and towards the elderly male population, less ready to refer to the doctors for help because of problems related to their mental health. With the aim to suicide prevention, doctors should become familiar with community, state and national resources that are concerned with youth and elderly populations, including mental health institutions, family and crisis intervention centers.
Keywords: suicide; gender identity; risk factors; serbia.